Managing the dead in disaster response: a matter for health security in the Asia-Pacific region?. Issue 6 (2nd November 2018) - Farrell, Anne-Maree
ABSTRACT: This paper explores the securitisation-desecuritisation nexus in managing threats to health, drawing on a case study examining the management of the dead in disaster response in the Asia-Pacific region. While securitising health threats may galvanise political action to address capacity, infrastructure and resource constraints, it is vital that the shift towards desecuritisation takes place once the immediate threat is under control. This is because desecuritisation is likely to create an environment in which established humanitarian, public health and forensic practices for addressing such threats can proceed in the context of normal politics. It will also offer greater flexibility for pursuing post-threat resilience strategies which will enhance individual and collective health and wellbeing. In turn, this may address broader human security concerns. Conceptualised in this way, resilience should be seen not merely as a strategy for resisting or adapting to a securitised situation but also as a key strategy to be deployed in the context of desecuritisation.